g(t) = -2t^3 – 2t^2 f(t)=t-3 Find g(-3) + f(-3) A) 32B) 10 C) 30 D) -30

Question

g(t) = -2t^3 – 2t^2
f(t)=t-3
Find g(-3) + f(-3)
A) 32B) 10
C) 30 D) -30

in progress 0
Harper 1 month 2021-10-16T04:56:26+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-16T04:58:17+00:00

    Answer:

    30

    Step-by-step explanation:

    g(t) = -2t^3 – 2t^2

    f(t)=t-3

    g(-3) = -2 (-3)^3 – 2(-3) ^2 =-2(-27) – 2(9) = 54 – 18 =36

    f(-3) = -3-3 = -6

    g(-3) + f(-3) = 36 + -6 = 30

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )